2011
DOI: 10.1016/j.ijpharm.2011.02.037
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo anti-tumor activities of a gemcitabine derivative carried by nanoparticles

Abstract: Gemcitabine (Gemzar®) is the first line treatment for pancreatic cancer and often used in combination therapy for non-small cell lung, ovarian, and metastatic breast cancers. Although extremely toxic to a variety of tumor cells in culture, the clinical outcome of gemcitabine treatment still needs improvement. In the present study, a new gemcitabine nanoparticle formulation was developed by incorporating a previously reported stearic acid amide derivative of gemcitabine into nanoparticles prepared from lecithin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
132
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(140 citation statements)
references
References 26 publications
(40 reference statements)
7
132
0
1
Order By: Relevance
“…90 Tokunaga Y et al The feasibility of adding GemC18 into other particles to overcome gemcitabine resistance in cancer cells has been evaluated recently in different studies. [93][94][95] GemC18 was incorporated into lipid nanoparticles (NPs) engineered from lecithin/glycerol monostearate-in-water emulsions. 93 In vitro studies were performed with a deficient hENT1 cell line (CCRF-CEM-AraC-8C).…”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
See 2 more Smart Citations
“…90 Tokunaga Y et al The feasibility of adding GemC18 into other particles to overcome gemcitabine resistance in cancer cells has been evaluated recently in different studies. [93][94][95] GemC18 was incorporated into lipid nanoparticles (NPs) engineered from lecithin/glycerol monostearate-in-water emulsions. 93 In vitro studies were performed with a deficient hENT1 cell line (CCRF-CEM-AraC-8C).…”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
“…[93][94][95] GemC18 was incorporated into lipid nanoparticles (NPs) engineered from lecithin/glycerol monostearate-in-water emulsions. 93 In vitro studies were performed with a deficient hENT1 cell line (CCRF-CEM-AraC-8C). 94 Native gemcitabine was not able to enter the cells efficiently, but the GemC18-NPs were able to efficiently deliver the stearoyl gemcitabine into cells by endocytosis and caused apoptosis via caspase-3 activation.…”
Section: Lipophilic Prodrugsmentioning
confidence: 99%
See 1 more Smart Citation
“…[177][178][179][180] For example, it was shown that conjugation of a fatty acid, such as stearic acid, to gemcitabine at the 4-N position decreases the sensitivity of the later to deaminase. 181,182 In addition, gemcitabine-fatty acid conjugates formulated into nanoparticles also become less sensitive to deamination, as they are no longer good substrates of CDAs. 182 Meng et al developed a MSNP for co-delivery of gemcitabine and paclitaxel to take advantage of paclitaxel's ability to inhibit CDA expression to increase tumor response to gemcitabine.…”
Section: Reducing Deamination Of Gemcitabinementioning
confidence: 99%
“…However, the evaluation at a cellular level is not comprehensive. For the sake of harvesting more reliable results, evaluating the effectiveness of the formulations at omnidirectional levels is necessary [18,19]. At a cellular level, evaluation has mainly involved the detection of cell apoptosis by various methods with integrated advantages [20,21].…”
mentioning
confidence: 99%